Entrepreneurial Financing for Women-Owned MSMEs: The Role of Financial Literacy, Inclusion, and Performance - Tuti Zakiyah; Wahyuni Windasari (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze how financial literacy and financial inclusion influence financing decisions among women-owned MSMEs in Indonesia, with financial and nonfinancial performance acting as moderating variables. Methodology/approach: A quantitative explanatory approach was employed using survey data from 345 female entrepreneurs operating MSMEs on Java Island. Data were collected through structured questionnaires with validated measurement scales and analyzed using Structural Equation Modeling with Partial Least Squares. Results: Financial literacy and financial inclusion significantly enhance financing decision-making among women entrepreneurs. Financial performance strengthens the relationship between financial capability, access, and funding choices, indicating that better financial conditions improve the effectiveness of financing strategies. Non-financial performance directly influences financing decisions and partially moderates the effect of financial literacy, suggesting that managerial capability and organizational readiness play important roles in funding behavior of investors. Conclusions: Financing decisions among female-entrepreneur-owned MSMEs are shaped by the interaction between financial knowledge, institutional access, and organizational performance. Limitations: This study focuses on women-owned MSMEs on Java Island and relies on self-reported survey data. Contributions: This study extends the contingency-based financial behavior perspective and offers practical insights for developing inclusive financing programs for women entrepreneurs.